The potential of damages induced by wind speed - Wan Mohd Asyraf, Wan Mohd Razali (2013)
Malaysia is located near the equator and natural disasters such as hurricanes, tsunamis and tornadoes usually not occur in Malaysia. Known as a tropical country, Malaysia was not excluding from the strong winds as tropical storms and monsoon phenomenon. Damage rate in Malaysia cause by storm hazard is seen quite a surprise. Currently, there is no properly guidance to identify the wind hazard location in Malaysia. Therefore, the main objective of this study is to produce the spatial wind speed map for the peninsular Malaysia. Furthermore, in this study, the mean wind speed data at each of the capital state from 2008 to 2012 were collected. Databases are establishing through the GIS techniques. GIS techniques were used to create the spatially database information. Average wind speeds of the regions are identified in peninsular Malaysia. From the result, the relationship between the average wind speed and damage ratio due to wind speed in Malaysia are show good agreement. Therefore, the results of this study can be used as a guideline in the future.